THE APPLICATION OF LEAN CONCEPT IN OUTPATIENT SERVICE AT MEDIKA UTAMA HOSPITAL BLITAR - Christianto, Deny (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
The Application Of Lean Concept In Outpatient Service at Medika Utama Hospital Blitar. This study aims to implement Lean Management principles in Medika Utama Hospital Blitar's outpatient services, with the primary objectives of waste reduction and value enhancement. The research employs observational methods, problem identification, and improvement planning. Data collection includes waste and value assessment, along with time measurements for each process. Techniques such as Value Stream Mapping (VSM) are utilized for waste identification and the implementation of Lean interventions to streamline processes. Overprocessing is identified as the main source of waste in outpatient services, followed by waiting, transportation, and defects. The study suggests interventions like the transition from manual to electronic medical records, the introduction of an online appointment system, and optimization of the prescription process to address these issues. Value Stream Mapping offers effective solutions for waste reduction and the improvement of outpatient service efficiency